Art of Power - Pelosi, Nancy, 1940- ([New York] : Simon & Schuster, 2024)
"The most powerful woman in American political history tells the story of her transformation from housewife to House Speaker--how she became a master legislator, a key partner to presidents, and the most visible leader of the Trump resistance."--
Keywords: Pelosi, Nancy, -- 1940-; Pelosi, Nancy, -- 1940- -- Career in politics; United States. -- Congress. -- Biography. -- Speakers; Biography. -- United States; Politics and government; Autobiographies